Hasil Belajar Materi Geografi Bab Keragaman Budaya di Indonesia Kelas XI Menggunakan Bahan ajar E-modul Berbasis Aplikasi Flipbook Maker - Yohanna, Yohanna; Sucahyanto, Sucahyanto; Hijrawadi, Sony Nugratama (Peneliti.net, 2024)
Conventional learning is still occurring, such as in schools in this study. Teachers and students still have to memorize a lot of theory in their subjects and often rely on school-provided books that are sometimes inconsistent within the same class. In this age of advanced technology, teachers are expected to keep up with the times and incorporate electronic media into their teaching methods. Therefore, this research aims to investigate whether the use of electronic teaching materials in the form of modules has an impact on student learning outcomes. The research employed a pre-experimental method, utilizing a single class, which was the experimental class, and employed the One Group Pretest-Posttest Design. Quantitative data analysis was used. Based on the research findings, there was a significant difference in student learning outcomes after different treatments were administered in the class. The average posttest scores were notably higher than the initial pretest scores, with a significant difference. The paired sample T-test results lead to the conclusion that the use of e-modules based on the Flipbook Maker application has an impact on the learning outcomes of 11th-grade students at SMAN 58 Jakarta.